2015
DOI: 10.1371/journal.pone.0116144
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Virological Failure and Suppression after Enhanced Adherence Counselling, in Children, Adolescents and Adults on Antiretroviral Therapy for HIV in Swaziland

Abstract: IntroductionThis study explores factors associated with virological detectability, and viral re-suppression after enhanced adherence counselling, in adults and children on antiretroviral therapy (ART) in Swaziland.MethodsThis descriptive study used laboratory data from 7/5/2012 to 30/9/2013, which were linked with the national ART database to provide information on time on ART and CD4 count; information on enhanced adherence counselling was obtained from file review in health facilities. Multivariable logistic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

52
188
10

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 198 publications
(250 citation statements)
references
References 11 publications
52
188
10
Order By: Relevance
“…Extra efforts should be taken to address adherence issues, develop routine adherence monitoring and take into account the children's age and disease status in order to avoid making unsuitable switch to second-line therapy especially when interpreting VL. In settings where feasible, consistent VL measurements and resistance genotyping are advised when dealing with suspected DR cases [38,42]. Newly developed diagnostic methods are platforms for improved quality of detections especially for minor variant DRMs [46].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Extra efforts should be taken to address adherence issues, develop routine adherence monitoring and take into account the children's age and disease status in order to avoid making unsuitable switch to second-line therapy especially when interpreting VL. In settings where feasible, consistent VL measurements and resistance genotyping are advised when dealing with suspected DR cases [38,42]. Newly developed diagnostic methods are platforms for improved quality of detections especially for minor variant DRMs [46].…”
Section: Resultsmentioning
confidence: 99%
“…At retesting, about half of the study population who were children and adolescents were less likely to achieve viral re-suppression. These findings suggested that those who did not re-suppressed are more likely to have resistance mutations [38][39][40]. A research carried out on children living with HIV in Rhodes Island, USA, reported high HIV-1 diversity with widespread drug resistance among ART-experienced participants [41].…”
Section: Monitoring Of Hiv Drug Resistancementioning
confidence: 98%
See 1 more Smart Citation
“…This is one of the limitations of self-reported data. A participant from Swaziland mentioned that the decision on policy would have been made based on analysis of routine data, irrespective of its publication in a journal, although publication increased the credibility of the findings: 31 This is a really an issue of how literally you expect respondents to take the question. If I answer the question as it was phrased, then the answer is no-it was not the study per se that led to policy change, but rather the use of routine data to feed the advocacy efforts of MSF and Clinton Health Access Initiative (Kigali, Rwanda)-this would have happened regardless of the study.…”
Section: Challenges In Evidence-policy Linkagementioning
confidence: 99%
“…Its continued positive clinical impact depends on taking more than 95% of prescribed doses (Jobanputra et al, 2015;WHO, 2013;Zoufaly et al, 2013;Bhattacharya & Dubey, 2011;MOH, 2007). Several factors affect the rate of treatment adherence among children including drug regimen, caregivers, and society and culture related factors (Castro, Gonzalez, & Perez, 2015;Haberer & Mellins, 2009) (Hagstromer, Lundstedt, Balcha, & Bjorkman, 2013;Muller et al, 2011), (Reda & Biadgilign, 2012).…”
Section: Introductionmentioning
confidence: 99%